Ultrasonic fatigue testing of AISI 304 and 316 stainless steels under environmental and immersion conditions (Fracture and Structural Integrity, 2024)
Ultrasonic fatigue tests were carried out on stainless steel AISI 316 and 304, under two modalities: at room temperature and in immersion (water for 316 and antifreeze for 304 steels); all tests were carried out with a loading ratio R=-1. The results obtained in the tests at room temperature (without immersion), for both materials exhibited a significant increase in temperature, leaving heat marks on the narrow section of the specimens. This phenomenon occurred due to the low coefficient of thermal conductivity of these stainless steels (16.2 W/ (m °K)), and the recorded temperatures were around 200 °C, generating instantaneous failure of material. Analyzes of fracture surfaces on specimens tested at room temperature reveal that crack initiation was related to the high temperature, causing alteration at the granular scale of the material, followed by a typical behavior crack propagation and failure. For specimens tested under immersion conditions, it was possible to reduce the temperature below 100 °C, which solved the problem of failure due to thermal effect. The results for 316 stainless steel immersed in water showed a fatigue life of 1.188×1010 cycles at188 MPa of stress loading in the specimen; while specimens subjected to 263 MPa stress showed a fatigue life of around 7×106 cycles, representing a significant reduction with an approximate factor of 1700. On the other hand, specimens of 304 stainless steel immersed in antifreeze with the lowest loading values of 169 MPa, showing an infinite ultrasonic fatigue life; while tests subjected to 263 MPa loading stress attains 3.62×106 cycles of ultrasonic fatigue life. The scanning electron microscopy visualizations for both cases of immersion tests showed that the initiation and propagation of the crack occurred on the surface of the specimens, exhibiting the typical mechanical fracture behavior without any apparent thermal influence.
Keywords: Gigacycle fatigue; Stainless steels; fracture mechanisms; Fracture surfaces